Optimization of Assignment Problems in Private Class Scheduling Using Graph Application - Wati, Hanifah Felisia; Wahyuningsih, Sapti; Ramadhan, Muhammad Nur (Jurusan Matematika FMIPA Universitas Pattimura, 2025)
The tutoring institution PT. Inspirasi Mandiri Nusantara (PINTARA) provides various types of learning services for students of various levels. The services offered include regular, intensive, exam preparation, and private classes. Private class services face scheduling problems due to the limited number of tutors and the mismatch between the availability of tutors and the subjects offered. This article discusses the optimization of tutor assignments using the maximum matching algorithm on bipartite graphs and the Hungarian algorithm. The study uses a mathematical approach and data is obtained through direct observation and modeled in the form of graphs, then solved with the Python program tool. The results show that optimal assignments can be achieved using the maximum matching algorithm, the Hungarian algorithm, and the Python program tool with the same and optimal values. This approach has proven effective and can be the basis for the development of an automatic scheduling system in the future.